2022
DOI: 10.21070/madrosatuna.v6i1.1564
|View full text |Cite
|
Sign up to set email alerts
|

Development of Minimum Competency Assessment (AKM)-Based Exercise Books to Improve Students' Literacy and Numeracy Skills at Sdn Janti 02 Sidoarjo

Abstract: Develop a Minimum Competency Assessment-Based Exercise Book to Improve Students' Literacy and Numerical Ability at SDN Janti 02 Sidoarjo to provide exciting and creative learning media in a lesson that aims to improve student learning outcomes. This is one of the reasons behind this development research. The study aimed to develop a minimum competency assessment-based exercise book to enhance students' literacy and numeracy skills at SDN Janti 02 Sidoarjo. This research and development method uses the research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
(10 reference statements)
0
1
0
1
Order By: Relevance
“…The results of the research showed that the questions developed were very good. The questions are adapted to the context that is relevant to the students there : 29-12-2023 Accepted: 05-02-2024 Approved: 18-02-2024 Published: 30-03-2024 15 produced AKM reading literacy questions (Nuril et al, 2022). The third research is entitled Development of a Minimum Competency Assessment (AKM) Based Practice Book to Improve Students' Literacy and Numeracy Abilities at SDN Janti 02 Sidoarjo.…”
Section: The First Research Was Entitled Development Of Ict-based Lit...mentioning
confidence: 99%
“…The results of the research showed that the questions developed were very good. The questions are adapted to the context that is relevant to the students there : 29-12-2023 Accepted: 05-02-2024 Approved: 18-02-2024 Published: 30-03-2024 15 produced AKM reading literacy questions (Nuril et al, 2022). The third research is entitled Development of a Minimum Competency Assessment (AKM) Based Practice Book to Improve Students' Literacy and Numeracy Abilities at SDN Janti 02 Sidoarjo.…”
Section: The First Research Was Entitled Development Of Ict-based Lit...mentioning
confidence: 99%
“…Hasil tes yang dilakukan oleh peneliti belum mencapai 50% dari keseluruhan siswa. Pada tahun 2022 penelitian serupa yang dilakukan oleh (Nuzulia & Gafur, 2022) juga menunjukkan adanya permasalahan yang dihadapi di Sekolah Dasar peneliti sesuai hasil observasi adalah rendahnya literasi membaca siswa. Kesulitan siswa di dalam berpikir kritis diketahui dengan minimnya siswa mengerjakan soal Higher Order Thinking Skills (HOTS) yang berbasis AKM (Nuzulia & Gafur, 2022).…”
Section: Pedahuluanunclassified